Analysis of Women’s Economic Empowerment in Sukabumi City - Iin Khairuunnisa; Endang Supriatna (LifeSciFi, 2018)
Facing the free market era, local governments need to make structural policies that support and provide incentives for the development and improvement of SME performance. The potential of women in social life has not yet received a reasonable portion. This needs to be handled wisely by the government considering women in terms of quantity ranks first in the composition of citizens. This type of research is a descriptive study with qualitative methods. The discussion in this article is the role of local governments to increase women’s empowerment in the economy by providing training in sewing skills, micro-credit business, and women’s leadership training for women. Skills training and microcredit business are provided to communities where the economic level is still below standard or underprivileged in order to improve family welfare through the efforts provided by the local government